Spinocerebellar Degeneration - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Two children, an 8-year old boy and a 6-year old girl, with progressive ataxia, dysmetria, hypoactive or absent deep tendon reflexes, equivocal plantar response, and sensory impairments, were investigated by pathologists and neurologists at the University of Vermont, Burlington, VT, and University of Saskatchewan, Saskatoon, Canada.